2017
DOI: 10.5662/wjm.v7.i3.108
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of crescent sign on ocular ultrasound in diagnosing papilledema

Abstract: AIMTo study the usefulness of orbital ultrasonography in the diagnosis of papilledema.METHODSFifty patients who were referred to the neurophthalmology clinic and clinically suspected to have papilledema were selected. Thorough, clinical examination with slitlamp biomicroscopy and visual acuity assessment was done. These patients underwent ultrasonography to demonstrate the crescent sign. The patients were further evaluated with the neurologist and magnetic resonance imaging (MRI) thus confirming the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…We noticed that all the patients with a positive crescent sign were having elevated ICP measuring (≥300 mmHg). In a recent study in India which was carried out by Bhosale et al in 2017,[20] and in another one in 2011 by Neudorfer et al ,[21] it was found that the sensitivity was higher, (92%) and (90%), respectively, but they did not count the specificity because all the patients in their studies were proved to have raised ICP.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that all the patients with a positive crescent sign were having elevated ICP measuring (≥300 mmHg). In a recent study in India which was carried out by Bhosale et al in 2017,[20] and in another one in 2011 by Neudorfer et al ,[21] it was found that the sensitivity was higher, (92%) and (90%), respectively, but they did not count the specificity because all the patients in their studies were proved to have raised ICP.…”
Section: Discussionmentioning
confidence: 99%
“…If this diameter is noted to be increased in primary gaze and diminishes by 25% in eccentric gaze (30° test), then increased subarachnoid fluid surrounding the optic nerve is presumed to be present and this finding is consistent with papilledema. [22] Presence of fluid around the optic nerve as a “crescent” or “doughnut” sign has been shown to be useful in confirming papilledema. [22]…”
Section: Discussionmentioning
confidence: 99%
“…[22] Presence of fluid around the optic nerve as a “crescent” or “doughnut” sign has been shown to be useful in confirming papilledema. [22]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 ] Alternatively, USG measurement of ONSD is also quite sensitive and specific for IH. [ 7 8 9 ] The choice of newer radiological modalities depends upon the availability of radiological investigations at hand. While USG is quick, its interpretation may vary from person to person, and even the same operator may have variation in the estimation of ONSD upon repeated attempts.…”
mentioning
confidence: 99%
“…[ 10 ] Acute and chronic IH may be differentiated with the help of the crescent sign on USG (seen in papilledema), which indicates chronicity. [ 8 ]…”
mentioning
confidence: 99%